Dominica. Annual report 2007 - Instituto Interamericano de Cooperación para la Agricultura (IICA) (IICA, 2021)
In 2007, the IICA Office in Dominica celebrated its 23rd anniversary of collaboration with the agricultural sector and rural communities of Dominica. In an effort to assess progress in the implementation of the National Agenda and inform national authorities, key stakeholders in agriculture and tourism, the private sector and civil society, a national report is presented contemplating the following sections; the state of agriculture and rural life in the Commonwealth of Dominica, results of the implementation of the National Agenda for Technical Cooperation in the Commonwealth of Dominica during 2007, inter-institutional cooperation, new opportunities for technical cooperation, and finally main activities organized by the IICA.